Relationship Between Postpartum Mother Characteristics with Postpartum Blues Events - Tonasih Tonasih; Vianty Mutya Sari (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2018)
The process of psychological adaptation has occurred during pregnancy, before the birth process and after childbirth. In that period, the anxiety of a woman can increase. Unique experience experienced by the mother after delivery as many as 85% of women experience mood disorders or mood after childbirth that can affect many things, especially responses or acceptance of newborns. (Saleha, 2013). This study aims to determine the relationship between postpartum maternal characteristics with postpartum blues events in Harjamukti District Work Area Cirebon City Year 2018. The type of this research is analytical with cross sectional approach. The population in this study is postpartum mothers 1-40 days found in Work Area Kecamatan Harjamukti City Cirebon period 1-20 January 2018 as many as 41 postpartum mothers. The result of the research is based on chi square statistic test obtained by the age of ρ value of 0,345, education with value ρ 0,499, job with value ρ equal to 0,448, parity with value ρ equal to 0,543 and family support with value ρ equal to 0,148 meaning that age, work, parity and family support have no significant relationship with postpartum blues events. Conclusion There was no significant relationship between maternal age, education, occupation, parity and family support with postpartum blues events. It is therefore necessary to monitor the health of the postpartum either through home visits by health workers or visits to health facilities by postpartum mothers to recognize early blues and anticipate and handle postpartum blues so as not to continue into depression.